ELEMENTS OF GREEK PHILOSOPHY - Appleton, R. B. (Reginald Bainbridge), 1886-1938. ([S.l.])
1 online resource
Keywords: The Elements of Greek Philosophy (1922) is an overview of the basic principles of Ancient Greek philosophy, tracing the developments of Greek thought from Thales of Miletus to Socrates, Plato and Aristotle.